Atrioventricular Block in Children - Igor A. Kovalev; Yuri M. Belozerov; Dinara I. Sadykova; Dina R. Sabirova; Lyudmila V. Yakovleva; Zulfiya R. Khabibrakhmanova; Andrey S. Sakerin (Union of pediatricians of Russia, 2018)
Rhythm and conduction disorders of the heart occupy one of the leading places in the structure of cardiovascular pathology in children. Atrioventricular block is the slowing down or loss of impulses from the atria to the ventricles. The team of authors presents clinical guidelines based on the principles of evidence-based medicine, including all stages of diagnosis and treatment of children with atrioventricular block. The use of guidelines in clinical practice will allow to choose the best strategy for the diagnosis and treatment of atrioventricular block for each individual patient.